Penentuan Tingkat Kesuburan Tanah Di Balai Penyuluhan Pertanian Perikanan Dan Kehutanan Dengan Menggunakan Algoritma Naive Bayes Dalam Data Mining - Feri Hari Utami (RJOCS (Riau Journal of Computer Science), 2015)
A soil fertility is the ground state of the system in which water, air and nutrients in a sufficient state of balance and available according to crop needs, whether physical, chemical and biological soil, in other words is the fertile soil when the soil contains usur-elements required by plants. These elements are the variables determined kusuburan soil absorption capacity, degree of saturation of wet, clay content, organic matter content. The purpose of this study as follows, Applying database processing determining soil fertility in Agricultural Extension Center Naive Bayes algorithm by using the most appropriate for the accuracy of the indicators that have been determined, the use of Naive Bayes classification method to use to determine the similarity between the characteristics of the data in the database selector klasfikasi to select criteria based soil fertility in anarea. Based on the results of the discussion and testing can be concluded as follows, Information Systems Programme determination of the type of soil and the expected data from the previous user is transformed into a computerized, Is information system a system of determining the type of land use Naive Bayes methods can be useful in the future